The Material Of Akidah And Akhlak In Shaping The Character Of 10th Grade Students At Mas Islamiyah Sunggal - Ayuni, Ayuni; Lubis, Sakban (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This study focuses on identifying the components utilized in shaping the character of 10th-grade students through the subject of Akidah Akhlak at MAS Islamiyah Sunggal. It also examines the supporting and inhibiting factors in the process of character formation in this context. As a core subject in Islamic education, Akidah Akhlak plays a significant role in shaping students' behavior, morals, and ethics. Through Akidah, students are taught to build a strong belief in Allah SWT and internalize values of faith. Meanwhile, Akhlak guides them toward cultivating noble behavior and commendable attitudes in their daily lives. This study employs a qualitative approach using a case study method. Data collection techniques include observation, interviews, and documentation. The participants of this research comprise teachers, students, and foundation administrators. The findings reveal that the Akidah Akhlak material at MAS Islamiyah Sunggal significantly contributes to character building among students, particularly in fostering honesty, responsibility, discipline, and empathy towards others.